Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Historical review and contribution to the knowledge of Amythas membranifera (Ampharetidae): an integrative perspective of an Antarctic polychaete - Orlemir Carrerette; Mônica A. V. Petti; Dong-U. Kim; Sandra Bromberg; Gilberto Bergamo; Paulo Y. G. Sumida; In-Young Ahn (Polar Biology, 2023)

The Great Amazon Reef System: A fact - Thomás N. S. Banha; Osmar J. Luiz; Nils E. Asp; Hudson T. Pinheiro; Rafael A. Magris; Ralf T. S. Cordeiro; Michel M. Mahiques; Miguel Mies; Vinicius J. Giglio; Claudia Y. Omachi; Eduardo Siegle; Luciane C. Nogueira; et al. (Frontiers in Marine Science, 2022)

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

Deep-Sea Habitats and Megafauna on the Slopes of the São Paulo Ridge, SW Atlantic - Jose Angel A. Perez; Lucas Gavazzoni; Luis Henrique P. de Souza; Paulo Y. Gomes Sumida; Hiroshi Kitazato (Frontiers in Marine Science, 2020)

Evidence against mutualism in an aeolid nudibranch associated with Symbiodiniaceae dinoflagellates - Estela A. Monteiro; Arthur Z. Güth; Thomás N. S. Banha; Paulo Y. G. Sumida; Miguel Mies (Symbiosis, 2019)

Multidisciplinary Scientific Cruise to the Rio Grande Rise - Luigi Jovane; James R. Hein; Isobel A. Yeo; Mariana Benites; Natascha M. Bergo; Paulo V. F. Corrêa; Daniel M. Couto; Ayrton D. Guimarães; Sarah A. Howarth; Henrique R. Miguel; Kira L. Mizell; Denise S. Moura; et al. (Frontiers in Marine Science, 2019)

In situ shifts of predominance between autotrophic and heterotrophic feeding in the reef-building coral Mussismilia hispida: an approach using fatty acid trophic markers - M. Mies; A. Z. Güth; A. A. Tenório; T. N. S. Banha; L. G. Waters; P. S. Polito; S. Taniguchi; M. C. Bícego; P. Y. G. Sumida (Coral Reefs, 2018)

Bleaching in reef invertebrate larvae associated with Symbiodinium strains within clades A–F - M. Mies; A. Z. Güth; C. B. Castro; D. O. Pires; E. N. Calderon; M. Pompeu; P. Y. G. Sumida (Marine Biology, 2018)

Production of three symbiosis-related fatty acids by Symbiodinium types in clades A–F associated with marine invertebrate larvae - M. Mies; A. B. Chaves-Filho; S. Miyamoto; A. Z. Güth; A. A. Tenório; C. B. Castro; D. O. Pires; E. N. Calderon; P. Y. G. Sumida (Coral Reefs, 2017)

Production in Giant Clam Aquaculture: Trends and Challenges - M. Mies; P. Dor; A. Z. Güth; P. Y. G. Sumida (Reviews in Fisheries Science & Aquaculture, 2017)

Molecular evidence of symbiotic activity between Symbiodinium and Tridacna maxima larvae - Miguel Mies; M. A. Van Sluys; C. J. Metcalfe; P. Y. G. Sumida (Symbiosis, 2017)

Cyst infection in autosomal dominant polycystic kidney disease: causative microorganisms and susceptibility to lipid-soluble antibiotics - T. Suwabe; H. Araoka; Y. Ubara; K. Kikuchi; R. Hazue; K. Mise; S. Hamanoue; T. Ueno; K. Sumida; N. Hayami; J. Hoshino; A. Imafuku; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Age-dependent cognitive impairment in a Drosophila Fragile X model and its pharmacological rescue - Catherine H. Choi; Sean M. J. McBride; Brian P. Schoenfeld; David A. Liebelt; David Ferreiro; Neal J. Ferrick; Paul Hinchey; Maria Kollaros; Rebecca L. Rudominer; Allison M. Terlizzi; Eric Koenigsberg; Yan Wang; et al. (Biogerontology, 2010)

Leaf litterfall and decomposition of different above- and belowground parts of birch (Betula ermanii) trees and dwarf bamboo (Sasa kurilensis) shrubs in a young secondary forest in Northern Japan - S. K. Tripathi; A. Sumida; H. Shibata; K. Ono; S. Uemura; Y. Kodama; T. Hara (Biology and Fertility of Soils, 2006)

Progesterone’s effects to reduce anxiety behavior of aged mice do not require actions via intracellular progestin receptors - C. A. Frye; K. Sumida; B. C. Dudek; J. P. Harney; J. P. Lydon; B. W. O’Malley; D. W. Pfaff; M. E. Rhodes (Psychopharmacology, 2006)

Inhibiting 5α-reductase in the amygdala attenuates antianxiety and antidepressive behavior of naturally receptive and hormone-primed ovariectomized rats - Alicia A. Walf; Kanako Sumida; Cheryl A. Frye (Psychopharmacology, 2006)

Mid-aged and aged wild-type and progestin receptor knockout (PRKO) mice demonstrate rapid progesterone and 3α,5α-THP-facilitated lordosis - C. A. Frye; K. Sumida; J. P. Lydon; B. W. O’Malley; D. W. Pfaff (Psychopharmacology, 2006)

Reproduction, dispersal and settlement of the bathyal ophiuroid Ophiocten gracilis in the NE Atlantic Ocean - P. Y. G. Sumida; P. A. Tyler; R. S. Lampitt; J. D. Gage (Marine Biology, 2000)

CYP2C19 genotypes and omeprazole metabolism after single and repeated dosing when combined with clarithromycin - Q. Zhou; I. Yamamoto; T. Fukuda; M. Ohno; A. Sumida; J. Azuma (European Journal of Clinical Pharmacology, 1999)